2001
DOI: 10.1111/j.0014-3820.2001.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Genetic Evolution in Mountain White-Crowned Sparrows: Song Dialects Are Associated With Population Structure

Abstract: Abstract. Bird song often varies geographically within a species; when this geographic variation has distinct boundaries, the shared song types are referred to as song dialects. How dialects are produced and their adaptive significance are longstanding problems in biology, with implications for the role of culture in the evolution and ecology of diverse organisms, including humans. Here we test the hypothesis that song dialect, a culturally transmitted trait, is related to the population genetic structure of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(66 citation statements)
references
References 52 publications
(47 reference statements)
2
64
0
Order By: Relevance
“…We looked for correlations between genetic, vocal and geographic distance matrices using Mantel and partial Mantel tests (Smouse et al 1986) as in previous studies (MacDougall-Shackleton and MacDougall-Shackleton 2001;Soha et al 2004;Whitehead et al 1998;Wright and Wilkinson 2001). These tests compute correlations between two matrices, or in the case of the partial test, the correlations between the residuals of two matrices that have been regressed on a third, thereby controlling for effects due to the third matrix (Smouse et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We looked for correlations between genetic, vocal and geographic distance matrices using Mantel and partial Mantel tests (Smouse et al 1986) as in previous studies (MacDougall-Shackleton and MacDougall-Shackleton 2001;Soha et al 2004;Whitehead et al 1998;Wright and Wilkinson 2001). These tests compute correlations between two matrices, or in the case of the partial test, the correlations between the residuals of two matrices that have been regressed on a third, thereby controlling for effects due to the third matrix (Smouse et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found that dialects do explain significant, if small, amounts of genetic variation. In the mountain subspecies of the white-crowned sparrow (Z. l. oriantha), MacDougall-Shackleton and MacDougall-Shackleton (2001) estimated that dialects accounted for 0.79% of observed genetic variance, versus a 0.51% geographic variance component. Outside the songbirds, Wright and Wilkinson (2001) sampled the mtDNA of similar numbers of amazon parrots (Amazona auropalliata) on either side of a dialect boundary, and found no evidence that haplotypes segregated by dialect.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in species that acquire their sexual or territorial signals by learning, exposure to heterospecific signals can influence the populational characteristics of signals produced by adults (Olofsson and Servedio 2008). Cultural processes contribute to form geographical patterns of song variation (McDougall-Shackleton and McDougall-Shackleton 2001) and in this case convergence is expected to depend on the ratio of species abundance. However, no relationship between song and phenotypic or genotypic index is predicted (Emlen et al 1975;Grant and Grant 1997).…”
Section: Cultural Transmissionmentioning
confidence: 99%
“…In most cases, the birds will respond more strongly to local songs (e.g. Baker et al 2001;MacDougall-Shackleton and MacDougall-Shackleton 2001;Wright and Dorin 2001;Nelson and Soha 2004b). On the other hand, our knowledge of the acoustic cues used for recognition of songs from local populations is still incomplete, which impedes our full understanding of dialect function (Nelson and Soha 2004a).…”
Section: Introductionmentioning
confidence: 99%